2016
DOI: 10.1177/1687814016651820
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure evolution in AZ61 alloy processed by equal channel angular pressing

Abstract: Magnesium and its alloys are finding increasing use in aerospace, automobile, nuclear, electrical, and structural engineering applications because of their high strength-to-weight ratio when compared to aluminum, titanium, and steel. In this work, AZ61 wrought magnesium alloy was processed using equal channel angular pressing at three different temperatures of 483, 523, and 573 K using up to four equal channel angular pressing passes. A microstructural study was conducted by measuring the average grain size af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…The intensity of the peak in the ECAP processed specimens at 598 K is lower than that of the as-received specimen. Also, it can be seen that there exists great difference on the magnitude of the peak intensity of ECAP processed specimen at 598 K for two and four passes this is mainly due to induced plastic strain during ECAP similar results has been observed by Avvari et al [24][25][26][27][28].…”
Section: X-ray Diffraction Analysissupporting
confidence: 82%
“…The intensity of the peak in the ECAP processed specimens at 598 K is lower than that of the as-received specimen. Also, it can be seen that there exists great difference on the magnitude of the peak intensity of ECAP processed specimen at 598 K for two and four passes this is mainly due to induced plastic strain during ECAP similar results has been observed by Avvari et al [24][25][26][27][28].…”
Section: X-ray Diffraction Analysissupporting
confidence: 82%
“…For example, on one hand, two AZ31 alloys with an initial grain size of 390 µm [50] and 48 µm [51] were refined to 3.5 µm and 3.9 µm after 4 passes at 250 and 240°C, respectively. On the other hand, the grain size of an AZ61 alloy decreased from ~ 60 μm to ~ 20 μm after 4 passes at 300 °C [53]. Besides, the reported investigations show that multi-step ECAP with gradually decreasing processing temperature promotes further grain refinement down to ~ 250 nm [3,5,11].…”
Section: Microstructural Evolution After Ecap Processingmentioning
confidence: 86%
“…Even with an as-cast and coarse initial microstructure which is not currently used in the literature for ECAP processing, the present investigation shows that the ECAP processing of the present as-cast Mg-0.3Ce alloy results in very good grain refinement compared to another Mg-based alloys. This excellent grain refinement has not been obtained in conventional Mg-Al based alloys such AZ31 and AZ61 (Mg-6Al-1Zn, wt.%) alloys [50][51][52][53], or in Mg-Zn-Ca-Mn alloy [54] and Mg-13Gd-4Y-2Zn-0.6Zr (wt.%) alloys [55] under similar ECAP processing conditions (i.e. ECAP via route Bc through 4 passes).…”
Section: Microstructural Evolution After Ecap Processingmentioning
confidence: 88%
“…The strain pass exerts little or no influence on grain refinement, which is at striking difference with the behavior of fcc and bcc metals A low extrusion temperature is beneficial for manufacturing a fine‐grained microstructure; however, for a certain extrusion speed, Ding et al observed a minimum extrusion temperature below which the billed could not be fabricated without surface cracks. Furthermore, for the lower the extrusion speed, the lower the minimum workable extrusion temperature was obtained.…”
Section: Grain Refinement In Magnesium Alloys By Spdmentioning
confidence: 99%